2008
DOI: 10.1097/ccm.0b013e3181743eeb
|View full text |Cite
|
Sign up to set email alerts
|

Accurate characterization of extravascular lung water in acute respiratory distress syndrome*

Abstract: Indexing EVLW to PBW or AdjBW reduces the number of ARDS patients with normal EVLW and correlates better to Lung Injury Score and oxygenation than using ActBW. Studies are needed to confirm the presumed superiority of this method for diagnosing ARDS and to determine the clinical treatment implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 38 publications
1
85
0
10
Order By: Relevance
“…[11][12][13] Some studies in adults have reported an association between the rise in EVLW, the occurence of ARDS, and the mortality of patients with severe sepsis. 14,15 In the present study, EVLW elevation in the colloid group was smaller than in the crystalloid group (Table 3). The increase in lung capillary permeability in sepsis causes a shifting of fluid into the interstitial space, resulting in EVLW elevation.…”
Section: Discussion Evlw Elevation In the Colloid And Crystalloid Groupmentioning
confidence: 79%
“…[11][12][13] Some studies in adults have reported an association between the rise in EVLW, the occurence of ARDS, and the mortality of patients with severe sepsis. 14,15 In the present study, EVLW elevation in the colloid group was smaller than in the crystalloid group (Table 3). The increase in lung capillary permeability in sepsis causes a shifting of fluid into the interstitial space, resulting in EVLW elevation.…”
Section: Discussion Evlw Elevation In the Colloid And Crystalloid Groupmentioning
confidence: 79%
“…По казано, что контроль динамики ВСВЛ в процессе лече ния уменьшает продолжительность ИВЛ и длитель ность пребывания больного в отделении реанимации, а также снижает летальность в группе больных с некар диогенным ОЛ. Повышение ИВСВЛ >10 мл/кг сопро вождается более чем 60% летальностью [19][20][21][22].…”
Section: индекс внесосудистой воды легких (ивсвл) и ин дексы проницаеunclassified
“…Результаты подобных исследо ваний можно трактовать либо как ошибки диагностики ОРДС (включение в группу больных без ОРДС больных с острым повреждением легких), либо как дефекты из мерения ИВСВЛ. Известно, что дилюционные методы имеют тенденцию к недооценке количества ВСВЛ при ОЛ вследствие неполного распределения термального индикатора в отечной жидкости, нарушений вентиляци онно перфузионных отношений, допущений в матема тическом аппарате PiCCO Plus [19][20][21][22][23][24].…”
Section: индекс внесосудистой воды легких (ивсвл) и ин дексы проницаеunclassified
“…A severe complication of pneumonia is systemic spreading of the invading pathogen finally resulting in acute respiratory distress syndrome (ARDS), septic shock and sepsis [37][38][39]. A plethora of clinical studies has shown that pathogenesis of ARDS and sepsis include the influx of protein-rich fluid into the air spaces as a consequence of increased permeability of the blood-air barrier leading to fatal lung edema formation [40][41][42][43]. Experimental studies in animals and cultured cells strengthened the hypothesis that junctional disruption of the lung barrier significantly contributes to a deleterious outcome [44][45][46].…”
Section: Pneumoniamentioning
confidence: 99%